Eco-friendly microwave-assisted green and rapid synthesis of well-stabilized gold and core–shell silver–gold nanoparticles. (20th January 2016) - El-Naggar, Mehrez E.; Shaheen, Tharwat I.; Fouda, Moustafa M.G.; Hebeish, Ali A.
Highlights: Microwave-aided technology for rapid and green preparation. Synthesis of AuNPs and as bimetallic core–shell nanoparticles (AgNPs–AuNPs). Using curdlan (CRD) biopolymer to perform the dual role of reducing and capping agents. Abstract: Herein, we present a new approach for the synthesis of gold nanoparticles (AuNPs) individually and as bimetallic core–shell nanoparticles (AgNPs–AuNPs). The novelty of the approach is further maximized by using curdlan (CRD) biopolymer to perform the dual role of reducing and capping agents and microwave-aided technology for affecting the said nanoparticles with varying concentrations in addition to those affected by precursor concentrations. Thus, for preparation of AuNPs, curdlan was solubilized in alkali solution followed by an addition of tetrachloroauric acid (HAuCl4 ). The curdlan solution containing HAuCl4 was then subjected to microwave radiation for up to 10 min. The optimum conditions obtained with the synthesis of AuNPs were employed for preparation of core–shell silver–gold nanoparticles by replacing definite portion of HAuCl4 with an equivalent portion of silver nitrate (AgNO3 ). The portion of AgNO3 was added initially and allowed to be reduced by virtue of the dual role of curdlan under microwave radiation. The corresponding portion of HAuCl4 was then added and allowed to complete the reaction. Characterization of AuNPs and AgNPs–AuNPs core–shell were made using UV–vis spectra, TEM, FTIR, XRD, zeta potential, and AFM analysis. Accordingly, strong peaks of the colloidal particles show surface plasmon resonance (SPR) at maximum wavelength of 540 nm, proving the formation of well-stabilized gold nanoparticles. TEM investigations reveal that the major size of AuNPs formed at different Au +3 concentration lie below 20 nm with narrow size distribution. Whilst, the SPR bands of AgNPs–AuNPs core–shell differ than those obtained from original AgNPs (420 nm) and AuNPs (540 nm). Such shifting due to SPR of Au nanoshell deposited onto AgNPs core was significantly affected by the variation of bimetallic ratios applied. TEM micrographs show variation in contrast between dark silver core and the lighter gold shell. Increasing the ratio of silver ions leads to significant decrease in zeta potential of the formed bimetallic core–shell. FT-IR discloses the interaction between CRD and metal nanoparticles, which could be the question of reducing and stabilizing metal and bimetallic nanoparticles. XRD patterns assume insufficient difference for the AuNPs and AgNPs–AuNPs core–shell samples due to close lattice constants of Ag and Au. Based on AFM, AuNPs and AgNPs–AuNPs core–shell exhibited good monodispersity with spherical particles possessing different sizes in the studied samples. The average sizes of both metal and bimetallic core–shell were found to be 52 and 45 nm, respectively.